Design of Automatic Battery Charger Using Forward DC-DC Converter for Solar Home Energy - Nur Vidia Laksmi B.; Muhammad Syahril Mubarok; Fithrotul Irda Amaliah; As’ad Shidqy Aziz; Daeng Rahmatullah; Dimas Herjuno; Muhammad Afnan Habibi (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
The utilization of solar energy as a renewable and environmentally friendly energy source, which is inexhaustible, is an ideal solution to meet the growing demand for electricity. Solar Home Energy refers to a house powered by solar energy. The solar energy is subsequently stored in batteries using a battery charger. In this paper, a forward DC-DC converter is used as a battery charger to supply power to a self-sufficient house from solar energy, stored in a 96 V 45 Ah battery. A fuzzy logic controller is employed to regulate the output of the forward DC-DC converter, ensuring a constant charging voltage according to the set point. The output of this project is designed for 110 V 4.5 A; however, in practice, the forward DC-DC converter only achieved a charging voltage of 100.5 V, resulting in an error of 8.63% from the planned value. Additionally, the charging current reached 1.4 A, leading to a significant error of 63.89% from the planned charging current.